Differences in predator composition alter the direction of structure‐mediated predation risk in macrophyte communities. Issue 11 (29th April 2014) - Farina, Simone; Arthur, Rohan; Pagès, Jordi F.; Prado, Patricia; Romero, Javier; Vergés, Adriana; Hyndes, Glenn; Heck, Ken L.; Glenos, Sybil; Alcoverro, Teresa
<x xml:space="preserve">Abstract</x> Structural complexity strongly influences the outcome of predator–prey interactions in benthic marine communities affecting both prey concealment and predator hunting efficacy. How habitat structure interacts with species‐specific differences in predatory style and antipredatory strategies may therefore be critical in determining higher trophic functions. We examined the role of structural complexity in mediating predator–prey interactions across several macrophyte habitats along a gradient of structural complexity in three different bioregions: western Mediterranean Sea (WMS), eastern Indian Ocean (EIO) and northern Gulf of Mexico (NGM). Using sea urchins as model prey, we measured survival rates of small (juveniles) and medium (young adults) size classes in different habitat zones: within the macrophyte habitat, along the edge and in bare sandy spaces. At each site we also measured structural variables and predator abundance. Generalised linear models identified biomass and predatory fish abundance as the main determinants of predation intensity but the efficiency of predation was also influenced by urchin size class. Interestingly though, the direction of structure‐mediated effects on predation risk was markedly different between habitats and bioregions. In WMS and NGM, where predation by roving fish was relatively high, structure served as a critical prey refuge, particularly for juvenile urchins. In contrast, in EIO, where roving fish predation was low, predation was generally higher inside structurally complex environments where sea stars were responsible for much of the predation. Larger prey were generally less affected by predation in all habitats, probably due to the absence of large predators. Overall, our results indicate that, while the structural complexity of habitats is critical in mediating predator–prey interactions, the direction of this mediation is strongly influenced by differences in predator composition. Whether the regional pool of predators is dominated by visual roving species or chemotactic benthic predators may determine if structure dampens or enhances the influence of top–down control in marine macrophyte communities.